2018
DOI: 10.1088/1361-651x/aae400
|View full text |Cite
|
Sign up to set email alerts
|

Angular-dependent interatomic potential for the binary Ni–Cr system

Abstract: A new interatomic potential has been developed for the Ni-Cr system in the angular-dependent potential (ADP) format by fitting the potential parameters to a set of experimental and first-principles data. The ADP potential reproduces a wide range of properties of both elements as well as binary alloys with reasonable accuracy, including thermal and mechanical properties, defects, melting points of Ni and Cr, and the Ni-Cr phase diagram. The potential can be used for atomistic simulations of solidification, mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 51 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…The amended Finnis Sinclair potential reported that this potential gave a good agreement of the predicted formation energies of mono-vacancy and self-interstitial of octahedral interstitial site with experimental and theoretical data confirms the validity of the amended Finnis Sinclair potential in pure V (Finnis and Sinclair, 1984). Furthermore, the agreement of defect properties and mechanical properties of this alloy (V-4Ti-4Cr) with experimental or other theoretical data also support the applicability of the amended Finnis Sinclair potential in Vrich ternary V-Ti-Cr alloys (Howells and Mishin, 2018;Daw and Baskes, 1984). In this work, the amended Finnis Sinclair potential was adopted as a reference potential to investigate thermo-mechanical properties of the V-5Cr-5Ti alloy.…”
Section: The Interatomic Potential For V-5cr-5ti Ternary Alloysupporting
confidence: 78%
“…The amended Finnis Sinclair potential reported that this potential gave a good agreement of the predicted formation energies of mono-vacancy and self-interstitial of octahedral interstitial site with experimental and theoretical data confirms the validity of the amended Finnis Sinclair potential in pure V (Finnis and Sinclair, 1984). Furthermore, the agreement of defect properties and mechanical properties of this alloy (V-4Ti-4Cr) with experimental or other theoretical data also support the applicability of the amended Finnis Sinclair potential in Vrich ternary V-Ti-Cr alloys (Howells and Mishin, 2018;Daw and Baskes, 1984). In this work, the amended Finnis Sinclair potential was adopted as a reference potential to investigate thermo-mechanical properties of the V-5Cr-5Ti alloy.…”
Section: The Interatomic Potential For V-5cr-5ti Ternary Alloysupporting
confidence: 78%
“…Using the accelerated ML model outlined in Fig. 3, we compute GB segregation energy spectra for 18 solutes 37,40,42,53,58,[75][76][77][78][79][80][81] in a 20x20x20 nm 3 Ni polycrystal of grain size 10 nm; the anti-segregation region (ΔE seg i >0) is shaded. The spectra are fitted to the skew-normal function Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The melting point calculation used the solid-liquid phase coexistence method [52,[62][63][64]. A simulation block containing the solid and liquid phases separated by a planar interface was coupled to a thermostat.…”
Section: Resultsmentioning
confidence: 99%